Introducing research methodology : thinking your way through your research project - Flick, Uwe. (Thousand Oaks : SAGE Publishing, 2020)
"Accessible and easy to understand, this book offers an encyclopaedi c introduction to research, showing you how to think about every stage involved in a research project. Equipping you with the tools you need t o understand research processes, it helps you get to grips with the con cepts behind qualitative research methodology - and be ready to apply t hem. Packed with examples that are directly relevant to the kind of res earch students undertake, this book helps you develop your academic and research skills and showcases how diverse research can be, with exampl es across different contexts and with different kinds of data. This thi rd edition offers: - Hands-on guidance about how to develop key academi c skills like critical thinking, effective writing and building an argu ment - Straightforward guidance about interpreting findings, assessing arguments and understanding the wider impact of your work that helps yo u step confidently into a researcher role - A complete overview of the challenges and opportunities involved in working with new forms of data like social media and online data Supported by a dynamic new website t hat offers templates for building arguments, additional case studies an d dos and don'ts videos, this book is the perfect companion for anyone looking for a clear introduction to research methodology"--
Includes bibliographical references and index.
Keywords: Social sciences -- Research -- Methodology; Research -- Methodology